KEPEMIMPINAN POLITIK PEREMPUAN DALAM LITERATUR ISLAM KLASIK - Ridwan Ridwan (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
discussion about the status of woman’s political leadership has produce pros and contra among ulama. There’s a lot ofargument from each group from theological, sociological, or historical perspective. Women’s self image in classical tafsir literature still havediscriminative attitude to woman, positioned as inferior creature and weak intellectuality. This bias interpretation brought up stigma thatwoman is not proper to bear certain task, especially role on public domain as in political field. Therefore, in order to enhance insight tointerpretation that have character gender responsive and humanistic, we shouldn’t only interpret with literal and legalistic aspect, but must bebroaden to contextual-emansipatory. Finally, result of interpretation didn’t escape from Islamic vision and mission as rahmatan lil alamin’sreligion.